Digitalization of city and digital copetencies of citizens - Lebedeva Еlena V.; Deniskina, Anna I. (Journal of the Belarusian State University. Sociology, 2020)
The article is aimed to analyse the tendencies of digital transformation of the temporary city. A sociological reconceptualisation of the term «smart city» is proposed, various stages in the evolution of the theoretical ideas about a smart city are distinguished. Based on empirical data, the key areas of digitalisation of the urban environment, as well as the social risks associated with these processes are identified (first of all, technostress as difficulties in adapting to a new digital reality). The article concludes with analysis of the role of the urban environment as a factor in the formation of digital competencies of citizens in everyday and professional practices.